Studi Analisis Awig-Awig Nelayan Lungkak - Wirasandi Wirasandi; Abdul Majid Junaidi; M Zainuddin; Rasyid Ridho Hamidy; Hary Murcahyanto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
The purpose of this study was to determine the form of attachment of Awig-awig, the fishing community of Lungkak village to the use of natural resources. The method used is descriptive qualitative research. The subject of this research is the fishing community of Lungkak village. The results showed that the Awig-awig of the Lungkak community had an attachment in terms of life as a fisherman with local rules or customary rules that were made on the basis of the togetherness of the Lungkak community with people outside the Lungkak hamlet area, the form of attachment Awig-awig was in consultation with the people around the village. Outer Cape. The conclusion of the study shows that the role of Awig-awig in lungkak fishermen is something that has become a separate entity in the lifestyle of lungkak fishermen from time to time which is always used as a standard of living for lungkak fishermen. Keywords: Analysis, Awig-awig, Lungkak Village